The economic stimuli required at this time - Espinoza-González, Yessica (2021)
The world is facing an unpredictable health and economic crisis, the economic impacts unleashed by this double crisis has made governments to implement economic plans to mitigate the damage caused by the drastic restrictions imposed for prevent the spread of the coronavirus. This article briefly points out the economic stimuli that some countries have implemented, the restrictions they must consider, and if their application has been effective.